2014
DOI: 10.1039/c4cs00030g
|View full text |Cite
|
Sign up to set email alerts
|

Structural modification strategies for the rational design of red/NIR region BODIPYs

Abstract: This review focuses on classifying different types of long wavelength absorbing BODIPY dyes based on the wide range of structural modification methods that have been adopted, and on tabulating their spectral and photophysical properties. The structure-property relationships are analyzed in depth with reference to molecular modeling calculations, so that the effectiveness of the different structural modification strategies for shifting the main BODIPY spectral bands to longer wavelengths can be readily compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
704
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,178 publications
(722 citation statements)
references
References 358 publications
(556 reference statements)
13
704
1
4
Order By: Relevance
“…6 Unmodied BODIPY absorbs and emits light at wavelengths in the visible spectral region ($500 nm). Through chemical modication, BODIPY absorption and emission can be shied toward lower energy by (1) appending p-conjugated groups, at the C1, C2 or C6, C7 positions of pyrrole units, hence extending p-conjugation of the system; (2) fusing an aromatic ring with the dipyrrane core by an intramolecular oxidative cyclohydrogenation; (3) direct functionalization by introduction of aryl group through double or triple bond into 2,6-positions (4) replacing carbon C8 with a nitrogen atom (aza-BODIPY dye family) (5) functionalizing at C3, C5 or C8 -positions to obtain aryl-, styryl-or alkynyl-substituted BODIPYs.…”
mentioning
confidence: 99%
“…6 Unmodied BODIPY absorbs and emits light at wavelengths in the visible spectral region ($500 nm). Through chemical modication, BODIPY absorption and emission can be shied toward lower energy by (1) appending p-conjugated groups, at the C1, C2 or C6, C7 positions of pyrrole units, hence extending p-conjugation of the system; (2) fusing an aromatic ring with the dipyrrane core by an intramolecular oxidative cyclohydrogenation; (3) direct functionalization by introduction of aryl group through double or triple bond into 2,6-positions (4) replacing carbon C8 with a nitrogen atom (aza-BODIPY dye family) (5) functionalizing at C3, C5 or C8 -positions to obtain aryl-, styryl-or alkynyl-substituted BODIPYs.…”
mentioning
confidence: 99%
“…MO calculations have demonstrated that there is a marked red-shift of the main spectral bands of aza-BODIPY dyes, since the LUMO has a large MO coefficient on the aza-nitrogen atom and this results in a marked narrowing of the HOMO-LUMO gap relative to the analogous BODIPYs (Figure 6). 11 The most important optical and photophysical properties of BODIPY dyes are retained, and so these compounds are potentially suitable for use in biomedical applications in the biological window. In a similar manner to what has been reported for fused-ring-expanded Pc analogues (Figures 2 and 3), significant issues were encountered with compound stability when 2,3-naphtho moieties were introduced at the pyrrole β -carbons.…”
Section: Resultsmentioning
confidence: 99%
“…These chemosensors are generally chromogenic and/or fluorescent probes, which efficiently change their photophysical properties in the presence of anions. Among numerous fluorophores, BODIPY dyes possess excellent photophysical properties and applications in the areas of anion sensors, metal probes, and pH indicators [14][15][16][17][18][19][20] . This versatile utility is due to the capacity to substitute the many positions of the BODIPY core in Figure 1.…”
Section: Introductionmentioning
confidence: 99%